Optimizing Curcumin SNEDDS via D-Optimal Design and Evaluating Wound Healing Efficacy in Wistar Rats - Setyawan, Ferdinta Daniasta; Herman; Imba, Farhan (Jurnal Jamu Indonesia, 2025)
Curcumin, a bioactive compound extracted from turmeric, exhibits extensive pharmacological properties, including anti-inflammatory and wound-healing activities. Nevertheless, its clinical application is hindered by low aqueous solubility and poor bioavailability. This study aimed to optimize a curcumin-loaded Self-Nanoemulsifying Drug Delivery System (SNEDDS) using a D-Optimal experimental design to improve its solubility, stability, and therapeutic efficacy. The SNEDDS formulation was developed by varying the proportions of oil, surfactant, and co-surfactant. The optimized formulation demonstrated a particle size of 120 nm and an encapsulation efficiency of 94.5%, significantly accelerating wound closure by 98% within 14 days in Wistar rats. These results highlight the potential of curcumin SNEDDS as an effective topical formulation for wound therapy.